Education on medically unexplained symptoms: a systematic review with a focus on cultural diversity and migrants - An Mariman; Peter Vermeir; Marta Csabai; Anne Weiland; Karen Stegers-Jager; Ruben Vermeir; Dirk Vogelaers (European Journal of Medical Research, 2023)
Key messages Current dominantly biomedical thinking hampers adequate management. A continuum of education and training focusing on a biopsychical approach is largely lacking and should be enhanced. Increasing competencies in intercultural communication in the different levels of health care is needed to address the additional complexity of MUS management in a context of increasing diversity. In view of the high prevalence of MUS and the obvious gaps detected, research and dedication of health care resources should be intensified.